On the efficiency consequences of tax transition reform: The case of WAEMU countries - (:unkn) unknown (My University, 2021)
Does the revenue replacement strategy of border taxes with domestic revenue collection increaseefficiency in collecting revenues in developing countries? This paper attempted to answer thequestion, by assessing the efficiency consequences of announcing a tax transition reform programin West African Economic and Monetary Union Countries (WAEMU). Through impactevaluation framework with propensity score and synthetic control, we find that, the announcementof this reform increases efficiency in mobilizing resources at WAEMU level as compared totheir counterfactual. Efficient mobilization of resources increases by near 4% around the reformagenda, and is achieved 3 years following the announcement of the reform. We also find that thereform improves tax oriented doing business indicators at the community level, by increasingthe contribution rate score of firms by 22 scales and reducing collection time scores by 4 scalesas compared to the best doing business practices on these indicators. The paper also evidencedthat the reform is overall working through tax discipline rather than tax morale channel in these countries.Furthermore, having implemented semi-autonomous revenue agency (SARA) and adoptedvalue-added tax (VAT) prior to the reform, fosters the revenue efficiency increasing effect of thereform, while the effect of adopting large taxpayers’ units (LTU) is found to be inconclusive.
Keywords: African Research